Phage biocontrol: Enhancing food safety through effective pathogen reduction - Pujato, Silvina Alicia; Briggiler-Marcó, Mariángeles; Mercanti, Diego Javier (Advances in food and nutrition research, 2025)
Bacteriophages (phages) are viruses that specifically target bacteria, offering a promising biocontrol strategy for food safety. Their high specificity enables precise pathogen elimination without disturbing beneficial microbiota. Historically overshadowed by antibiotics, phage biocontrol is now regaining interest due to the rise of multidrug-resistant bacteria and increasing food safety concerns. Phages effectively reduce foodborne pathogens such as Escherichia coli O157:H7, Salmonella enterica, and Listeria monocytogenes in fresh produce, meat, and dairy products. Phage-based interventions can be applied pre- and post-harvest, acting as direct antimicrobial agents or as enhancers of existing preservation methods. Furthermore, phages offer advantages in combating biofilms, a major concern in food processing facilities. Despite their potential, challenges such as bacterial resistance, regulatory constraints, and large-scale production hurdles remain. This chapter discusses the evolution of phage biocontrol, its applications in food safety, and the challenges that must be addressed for its widespread adoption. Phages represent an innovative, eco-friendly alternative to conventional antimicrobials, aligning with the global demand for safer and more sustainable food production practices.